A look writing (Palíndromo, 2021)
This is an experimental text around the ideas of “writing” and “collective” as pervasive actions. To raise more questions about this hypothesis, paragraphs concatenate phrases uttered by people on the streets, for hours of walking, in a performative action.
Keywords: orality; graphocentrism; performance